Innovative Distribution Channels of Banking Services from the Customer’s Perspective - Fijołek, Karolina (Journal of Finance and Financial Law, 2016)
The article aims to provide how electronic distribution channels and more and more modern products are changing the face of banking. The transformation is about customer expectations, ways to cooperate with them, but also the bank’s internal processes. Banking has become increasingly dependent on the Internet and information systems – at present the majority of services offered is based on the network. In connection with this fact also are changing the organizational structures of banks and required skills of employees.